2021
DOI: 10.3390/ijerph18147487
|View full text |Cite
|
Sign up to set email alerts
|

Social-Economic Environments and Depressive Symptoms in Community-Dwelling Adults: A Multi-Level Analysis for Two Nationwide Datasets in Taiwan

Abstract: Most studies have focused on factors associated with depression at the individual level, and evidence on ecological models linking social-economic features with depression is rare in Taiwan. This study aimed to use multi-level analysis to explore the effects of social-economic environments on depressive symptoms among Taiwanese adults. The 2009 National Health Interview Survey (NHIS) and the Age-Friendly Environments database were linked in this study. A total of 6602 adults aged 20 years and older were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, the effect of these factors was different according to gender and age group. Economic environments were critical for men and young adults aged 20–44, while social environments were significant for women and middle-aged and older adults [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of these factors was different according to gender and age group. Economic environments were critical for men and young adults aged 20–44, while social environments were significant for women and middle-aged and older adults [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its onset ranges from mid-adolescence to middle age [1], and there is an increasing trend of depression internationally in the college student population [2]. In Taiwan, 15.1% of a community sample reported depressive symptoms, with younger age (those in an age group of 20 to 44) being a variable significantly related to a higher depression rate [3]. Apart from psychiatric and psychological interventions as treatments, systematic review and meta-analysis has revealed the effects of nature-based interventions on mental health [4], depression, and anxiety [5].…”
Section: Introductionmentioning
confidence: 99%